A practical home furnishing estimate - Morton, Caroline (My University, 1906)
Introduction: The expenditure of some real thought and interest in the planning and furnishing of our middle-class homes would give greater returns in real livableness than can be estimated. If we would but strive for simplicity and fitness of things, we should have real homes rather than the usual over-furnished homes that we put forth so much effort to care for. The ideal home is a place in which every member of the family can really live, grow, rest, and enjoy life, and every home should be planned and furnished on such a basis. We give here an excellent plan for a small house, which can be made into an ideal home for a small family. This plan will be used as the background for planning and estimating the cost of furnishings for any moderate home.
Citation: Morton, Caroline. A practical home furnishing estimate. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Home Economics; Home Furnishings; Furniture; Interior Design; Floor Plans; Theses